Grid-tie three-phase inverter with active and reactive power flow control capability - Sampaio, Leonardo Poltronieri; De Brito, Moacyr Aureliano Gomes [UNESP]; De Azevedo E Melo, Guilherme [UNESP]; Canesin, Carlos Alberto [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper proposes a methodology for the active and reactive power flow control, applied to three-phase inverter operating in grid-connected mode at low AC voltage. The converter's control technique is based on Linear Matrix Inequalities - LMI together with D-stability criteria and state-feedback linearization. Through multi-loop control, the power loop uses an adapted active and reactive power transfer expressions, in order to obtain the magnitude voltage and power transfer angle to control the power flow between the distributed generation and the utility/grid. The multi-loop control uses the technique of state-feedback linearization in order to minimize the system nonlinearities, improving the controller's performance and mitigating potential system disturbances. Moreover, the purpose of the methodology is to obtain the best controllers with the lowest gains placing the poles in the left-half s-plane region specified during the design stage, resulting fast responses with reduced oscillations. In order to demonstrate the feasibility of the proposed control a 3000VA three-phase prototype was experimentally implemented. Furthermore, experimental results demonstrate anti-islanding detection and protection against over/under voltage and frequency. © 2013 IEEE.
Keywords: Distributed Generation; Feedback Linearization; Linear Matrix Inequalities; Microgrid; Power Flow Control; Robust Control